High-capacity low-expansion porous silicon carbon material and preparation method thereof

By employing a multi-step vapor-phase silicon source deposition process and the use of specific organic solvents, the problem of excessive silicon deposition and expansion in porous carbon materials was solved, resulting in high-capacity, low-expansion silicon-carbon materials and improved battery cycle performance.

CN120922878APending Publication Date: 2025-11-11XIANTAO HAIRONG NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511070980.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

In the prior art, during the deposition of vapor-phase silicon sources on porous carbon with low pore volume and high porosity, crystallization inside the porous carbon pores and excessive deposition of vapor-phase silicon sources on the outer surface are prone to occur, resulting in excessive expansion of silicon-carbon materials, increased impedance, and thus affecting battery cycle performance.

Method used

A multi-step vapor-phase silicon source deposition process is adopted, and an organic solvent with specific cross-linking or adsorption capabilities is used to adsorb or bond the vapor-phase silicon source and its deposition intermediates to the surface of the porous carbon inner layer. The organic solvent is then decomposed and carbonized at high temperature to isolate the deposited silicon from direct contact with the secondary introduced vapor-phase silicon source. The second solvent forms a coating of the vapor-phase carbon source, which suppresses the expansion of the internal silicon layer.

Benefits of technology

This technology enables the deposition of silicon with high loading and uniform amorphous inner layers on porous carbon substrates with low pore volume and high microporosity, thereby reducing the impedance of the material and improving the cycle life and capacity retention of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005528128650000171
    Figure BDA0005528128650000171
  • Figure HDA0005528128660000011
    Figure HDA0005528128660000011
  • Figure HDA0005528128660000012
    Figure HDA0005528128660000012
Patent Text Reader

Abstract

A preparation method of a high-capacity low-expansion porous silicon-carbon material comprises the following steps: introducing a gas-phase silicon source into porous carbon heated to a first deposition temperature to obtain porous carbon with part of silicon deposited, cooling to below the boiling point of a first solvent, uniformly mixing the first solvent with the porous carbon, heating and introducing the gas-phase silicon source to obtain a porous silicon-carbon intermediate; uniformly mixing a second solvent with the porous silicon carbon intermediate which is reduced to be below the boiling point of the second solvent, heating to a second deposition temperature, and introducing a gas-phase carbon source and inert gas to obtain a high-capacity low-expansion porous silicon carbon material; the first solvent can physically and / or chemically adsorb a gas-phase silicon source and link part of a silicon deposition layer in porous carbon deposited by silicon, and the second solvent can physically and / or chemically adsorb a gas-phase carbon source and a silicon deposition layer linked with a porous carbon intermediate; the first solvent and the second solvent are organic solvents of which the boiling point and the cracking temperature are lower than the deposition temperature, and the porous silicon carbon material with high silicon load, high energy density and long cycle life is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of silicon-carbon materials technology, and in particular to a high-capacity, low-expansion porous silicon-carbon material and its preparation method. Background Technology

[0002] With the development of new energy technologies, the energy density requirements for lithium-ion batteries are increasing. Traditional graphite anodes, with a theoretical specific capacity of only 372 mAh / g, have essentially reached their limit and are unlikely to achieve further breakthroughs, failing to meet the demands for higher energy density. Therefore, the development of novel anode materials is urgently needed. To further improve battery energy density, a redesign from a materials perspective is required. Silicon-based anodes have higher capacity, with a theoretical capacity reaching 4200 mAh / g (based on Li). 4.4 Si (calculated) has become an ideal candidate. The commonly used preparation method in the market is to use silane CVD vapor deposition technology, in which elemental silicon produced by silane cracking is deposited inside porous carbon. The pores of the porous carbon reserve space for the expansion of silicon during the charging and discharging process of the battery.

[0003] However, in most cases, due to the need to maintain a high microporosity (≥80%), the pore volume of porous carbon is limited, and the pore volume of commercially available porous carbon is generally low, usually less than 1 cm. 3 When a high silicon deposition rate is required, such as a SiH4:porous carbon mass ratio of >55:45, excessive silicon will be deposited on the outer surface of the porous carbon, resulting in high resistivity. Simultaneously, the silicon-carbon material expands significantly during full electric cycling, accelerating capacity decay and potentially leading to cycle failure. On the other hand, simply increasing the pore volume will result in a larger average pore size and lower microporosity. After silicon is deposited on the inner surface, silicon crystallization is likely to occur during subsequent deposition. Furthermore, silanes are easily adsorbed onto the outer surface of the porous carbon for deposition, which also easily leads to significant expansion during full electric cycling, resulting in cycle failure.

[0004] Therefore, in order to overcome the existing technological bottlenecks, it is necessary to develop a new type of high-capacity, low-expansion porous silicon-carbon material and its preparation method. While maintaining a low pore volume, it is necessary to precisely control the silicon deposition process on a porous carbon substrate with a high microporosity, ensuring that silicon is deposited uniformly and amorphously on the inner surface, avoiding silicon crystallization in the inner layer of porous carbon and deposition on the outer surface, effectively suppressing the uncontrollable expansion of silicon particles during cycling, and obtaining a porous silicon-carbon material with high silicon loading, high energy density and long cycle life. Summary of the Invention

[0005] In order to solve the problems in the prior art of vapor deposition of silicon sources on porous carbon with low pore volume and high porosity, such as crystallization inside the porous carbon pores and excessive deposition of silicon sources on the outer surface, as well as the excessive expansion of silicon-carbon materials caused by this phenomenon, resulting in increased impedance and ultimately reduced battery cycle performance, this invention proposes a multi-step vapor deposition scheme for silicon sources. This invention innovatively proposes a technical solution completely different from direct vapor deposition coating. It adopts a multi-step vapor-phase silicon source deposition process and innovatively utilizes organic solvents with specific cross-linking or adsorption capabilities based on the state and properties of the vapor-phase silicon source during porous carbon deposition. This allows the vapor-phase silicon source and its vapor deposition intermediates to be more adsorbed or bonded to the inner surface of the porous carbon through physical or chemical actions. Combined with the fixation and coating effect of the organic solvent's high-temperature cracking and carbonization, direct contact between the deposited silicon and the secondary introduced vapor-phase silicon source is isolated, avoiding silicon crystallization inside the porous carbon. Furthermore, another organic solvent with the ability to cross-link and adsorb both the deposited silicon and the vapor-phase carbon source in the porous silicon-carbon intermediates is used to further coat the silicon-carbon material after the vapor-phase carbon source is carbonized, suppressing the expansion of the internal silicon layer, thereby reducing impedance and further improving the cycle life of the battery.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0007] This invention provides a method for preparing a high-capacity, low-expansion porous silicon-carbon material, comprising the following steps:

[0008] S1: A gaseous silicon source is introduced into the porous carbon heated to the first deposition temperature to carry out a gaseous silicon source deposition reaction, and a partially silicon-deposited porous carbon is obtained. The temperature is lowered to below the boiling point of the first solvent, and the first solvent is mixed evenly with the partially silicon-deposited porous carbon. After heating to the first deposition temperature, a gaseous silicon source is introduced again to carry out a gaseous silicon source deposition reaction, and a porous silicon-carbon intermediate is obtained.

[0009] S2: The second solvent is mixed evenly with the porous silicon-carbon intermediate cooled to below the boiling point of the second solvent. After heating to the second deposition temperature, a mixture of gaseous carbon source and inert gas is introduced to carry out gaseous carbon source deposition reaction, and high-capacity, low-expansion porous silicon-carbon material is obtained.

[0010] The first solvent is an organic solvent that can adsorb the silicon deposition layer in the porous carbon containing the gaseous silicon source and the partially deposited silicon through physical and / or chemical means, and whose boiling point and decomposition temperature are lower than the first deposition temperature.

[0011] The second solvent is an organic solvent that can adsorb gaseous carbon sources and link porous carbon intermediates in a silicon deposition layer through physical and / or chemical means, and whose boiling point and decomposition temperature are lower than the second deposition temperature.

[0012] The first solvent and the second solvent may be the same or different solvents. The first deposition temperature and the second deposition temperature are not specifically limited, nor are they restricted to the numerical ranges listed in this specification. Those skilled in the art can understand the thermal decomposition characteristics of the gaseous silicon source and gaseous carbon source based on common knowledge, obtain the thermal decomposition temperature, and optimize the deposition temperature range through conventional experiments to ensure effective decomposition of the gaseous material at the deposition temperature and controllable deposition on the porous carbon surface. For example, the first deposition temperature and the second deposition temperature are each independently a temperature between 350 and 700°C.

[0013] This invention employs a multi-step vapor-phase silicon source deposition strategy and innovatively combines a first solvent and a second solvent to suppress silicon crystallization inside porous carbon pores and excessive deposition on the outer surface of porous carbon. This overcomes the problem that excessive silicon deposition on the outer surface of porous carbon leads to high material resistivity, while the silicon-carbon material expands significantly during full electric cycling, resulting in rapid capacity decay and cycle failure.

[0014] The first solvent exhibits strong physical adsorption and / or chemical cross-linking capabilities with the fumed silicon source and its deposited silicon layer. This capability stems from the strong physical adsorption and cross-linking bonding of the organic solvent with the fumed silicon source and its deposited product. In this case, a two-step fumed silicon source deposition process is performed in S1. In the first step, the fumed silicon source is preferentially deposited within the pores of the porous carbon, while the first solvent is more readily adsorbed within the porous carbon. When the temperature is raised to the first deposition temperature, since the decomposition temperature of the first solvent used in this invention is lower than the deposition temperature of the fumed silicon source, the first solvent can undergo decomposition and carbonization during the heating process, thus avoiding the need for a second introduction of solvent. The fumed silicon source directly contacts the elemental silicon in the semi-deposited silicon-carbon, inhibiting silicon crystallization inside the porous carbon and effectively adsorbing the fumed silicon source into the inner pores. Furthermore, the addition of a second solvent allows for better penetration into the pores of the porous carbon intermediate, as the second solvent simultaneously adsorbs or crosslinks the silicon deposition layer and the fumed carbon source. This allows the second solvent to better evaporate, reducing the amount of exposed silicon inside the porous carbon, buffering silicon expansion, lowering impedance, and ultimately improving cycle performance.

[0015] As a further embodiment, the first solvent is selected from organic solvents with a boiling point of 60 to 300°C that can adsorb silicon deposits in porous carbon containing gaseous silicon sources and partial silicon deposits through physical and / or chemical means.

[0016] As a further embodiment, the first solvent is exemplary selected from one of acetonitrile, formamide, glycerol, propylene carbonate, dimethyl sulfoxide, ethylene glycol, dimethylformamide, and nitromethane.

[0017] This invention further optimizes the type of the first solvent, comprehensively considering its boiling point, adsorption capacity for the fumed silicon source, and physical adsorption and chemical bonding capacity for the silicon deposited layer. A higher boiling point of the first solvent shortens the heating time required before the second fumed silicon source is introduced, thereby reducing the volatilization of the first solvent within the porous carbon pores. Furthermore, the type of the first solvent is further optimized based on its adsorption and cross-linking effects on the silicon deposited layer in the porous carbon, ensuring better adsorption and cross-linking of the silicon deposited layer. The combined optimization of these factors enhances the penetration of the first solvent within the porous carbon pores, increases solvent volatilization on the porous carbon surface, and reduces solvent volatilization within the porous carbon pores. This enhances the adsorption of the introduced fumed silicon source within the pores and reduces the deposition of the fumed silicon source on the outer surface of the porous carbon, thereby further reducing the impedance of the silicon-carbon material and improving capacity cycling retention.

[0018] As a further preferred embodiment, the first solvent is selected from organic solvents with a boiling point of 150 to 300°C.

[0019] As a further preferred embodiment, the first solvent is exemplary selected from one or more of glycerol, formamide, dimethyl sulfoxide, and propylene carbonate.

[0020] As a further embodiment, before the first solvent is added in S1, the flow rate of the gaseous silicon source is 6-10 L / min, and the time for introducing the gaseous silicon source and keeping it at a temperature is 96-160 min.

[0021] After the first solvent is added in S1, the flow rate of the gaseous silicon source is 5-8 L / min, and the time for introducing the gaseous silicon source and keeping it at a constant temperature is 45-72 min.

[0022] In this invention, the utilization rate of the fumed silicon source can be further controlled by controlling the flow rate of the two fumed silicon sources, thereby controlling the amount of silicon deposited on the porous carbon material. A higher flow rate results in lower utilization of the fumed silicon source, ultimately leading to a decrease in the amount of deposited silicon, resulting in a lower capacity of the silicon-carbon material. Conversely, a lower flow rate, while increasing silicon deposition and thus the capacity of the silicon-carbon material, causes excessively low flow rates to deposit more fumed silicon on the porous carbon surface, leading to expansion and higher resistivity of the silicon-carbon material. Therefore, limiting the flow rate of the fumed silicon source within a certain range can further optimize the amount of silicon deposited on the porous carbon material. Under the action of the first solvent, this optimization of the fumed silicon source flow rate can further reduce the amount of silicon deposited on the outer surface of the silicon-carbon material, lower the impedance, and improve the cycle capacity retention rate. By controlling the time of introducing the gaseous silicon source twice before and after the first solvent is added, and maintaining the temperature, the amount of gaseous silicon source deposited on porous carbon before and after the first solvent is introduced can be regulated. This avoids excessive deposition of gaseous silicon source on the outer surface of porous carbon due to excessive first-time introduction, and also avoids insufficient deposition of gaseous silicon source in the pores of porous carbon due to insufficient first-time introduction. In this case, the first solvent cannot be well adsorbed onto the silicon deposition layer, reducing the amount of carbonization of the first solvent on the silicon deposition layer. As a result, the second gaseous silicon source deposition is more likely to directly contact the deposition layer formed during the first gaseous silicon source deposition, increasing the risk of silicon crystallization, which in turn leads to increased impedance and reduced cycle capacity retention.

[0023] As a further embodiment, the solid-liquid ratio of the first solvent to the porous carbon introduced by the gas phase silicon source is (88-93):(7-12).

[0024] The present invention further optimizes the amount of the first solvent to avoid the first solvent being too low, which would result in the first solvent adsorbing too little of the product deposited by the vapor silicon source, thereby affecting the more of the vapor silicon source adsorbed inside the porous carbon.

[0025] As a further embodiment, the cooling temperature in S1 is 1 to 40°C below the boiling point of the first solvent.

[0026] As a further embodiment, the heating rate in S1 to reheat to the first deposition temperature is 40–70 °C / min.

[0027] This invention further limits the cooling temperature. When the cooling temperature is too low, the heating time during the second introduction of the gas-phase silicon source is too long, resulting in more solvent evaporation in the porous carbon inner layer and more silane deposition on the porous carbon surface, leading to greater expansion. Conversely, when the cooling temperature is too high, some of the first solvent may evaporate during the addition process due to excessive temperature. In this case, the amount of the first solvent entering the porous carbon is too small, leading to the same result as the former. Similarly, when the heating rate during the second deposition of the gas-phase silicon source is too low, more solvent evaporation occurs in the porous carbon inner layer, more silane from the gas-phase silicon source is deposited on the surface, leading to greater expansion and higher resistivity. When the heating rate is too high, power consumption increases, affecting the lifespan of the equipment.

[0028] As a further embodiment, the second solvent is selected from organic solvents with a boiling point of 60 to 300°C and having a silicon deposition layer that adsorbs gaseous carbon sources and links porous carbon intermediates through physical and / or chemical means.

[0029] As a further embodiment, the second solvent is exemplary selected from one or more of toluene, chloroform, PolarClean, cyclohexane, benzene, and aniline.

[0030] The PolarClean is a mixture of methyl 5-(dimethylamino)-2-methyl-5-oxovalerate (1) and N,N,N',N'-2-pentamethylglutaramide (2) in a mass ratio of 20:1.

[0031] As a further option, the second solvent is selected from organic solvents with a boiling point of 100 to 280°C.

[0032] As a further embodiment, the solid-liquid ratio of the second solvent to the porous carbon intermediate is (88-93):(7-12).

[0033] As a further embodiment, the cooling temperature in S2 is 1 to 40°C below the boiling point of the second solvent.

[0034] As a further embodiment, the heating rate in S2 to the second deposition temperature is 40–70 °C / min.

[0035] As a further embodiment, the flow rate of the gaseous carbon source introduced in S2 is 6-10 L / min, and the gaseous carbon source is introduced and kept at a temperature for 96-160 min.

[0036] In this invention, by individually or simultaneously optimizing factors such as the temperature at which the second solvent is cooled to below its boiling point, the rate at which the temperature is raised to the temperature at which the gaseous carbon source is deposited, and the flow rate of the gaseous carbon source, the adsorption capacity of the gaseous carbon source inside the porous carbon can also be affected. This is related to factors such as the volatilization of the second solvent during the heating process and the amount of gaseous carbon source deposited.

[0037] As a further embodiment, the porous carbon has a pore volume of 0.8 ± 0.3 cm³. 3 / g, the microporosity of porous carbon is ≥80%.

[0038] The microporosity refers to the percentage of pores with an average pore size <2 nm in porous carbon, which constitutes the total pore volume.

[0039] This invention can further limit the parameters such as pore volume and microporosity of porous carbon. When the pore volume and microporosity are within a certain range, the appropriate pore volume and microporosity provide sufficient space for the deposition of gaseous silicon source inside the pores of porous carbon. It also avoids the phenomenon that the pore volume is too low and exceeds the limit of silicon deposition. In this case, silicon may be mainly deposited on the surface in the later stage, resulting in a large silicon content on the surface, excessive expansion, high resistivity and other problems. It also avoids the problem that the pore volume of porous carbon is too large. In this case, the microporosity is low, more silicon is deposited on the surface, silicon crystallization is easy to occur, and the resistivity increases.

[0040] As a further preferred embodiment, the specific surface area of ​​the porous carbon is 1500–2500 m². 2 / g.

[0041] As a further preferred embodiment, the porous carbon has a particle size of 2–10 μm and an average pore size of 1–5 nm.

[0042] As a further embodiment, the gaseous silicon source includes halogen-free silane gaseous silicon sources and halogen-containing silane gaseous silicon sources.

[0043] As a further option, the halogen-free silane-based gaseous silicon source includes one of silane, ethylsilane, and propane.

[0044] As a further option, the halogenated silane gaseous silicon source is selected from one or more of dichlorosilane, trichlorosilane, tetrachlorosilane, and methyltrichlorosilane.

[0045] As a further preferred embodiment, the gaseous silicon source is a silane-based gaseous silicon source.

[0046] As a further preferred embodiment, the gaseous silicon source is silane.

[0047] As a further embodiment, the gaseous carbon source is exemplary selected from one or more of acetylene, ethylene, propylene, methane, ethane, and propane.

[0048] As a further preferred embodiment, the gaseous silicon source is silane, the gaseous carbon source is acetylene, the first solvent is glycerol, the second solvent is PolarClean, the cooling temperature in S1 is 1-20°C below the boiling point of the first solvent, the cooling temperature in S2 is 1-20°C below the boiling point of the second solvent, and the heating rate in S2 to reheat to the first and second deposition temperatures is 55-70°C / min.

[0049] This invention further limits the types of the first and second solvents based on the physicochemical properties of the selected gaseous silicon and carbon sources. Both the first and second solvents are high-boiling-point organic solvents. Because the first solvent, glycerol, has a high penetration effect on the deposited silicon layer of silane and contains numerous chemical groups that bind to the deposited silicon layer, it facilitates the wetting of glycerol within the porous carbon pores and its cross-linking with part of the deposited silicon layer. Simultaneously, by controlling the cooling temperature within a certain range below the boiling point of the first solvent, the difference between the cooling temperature and the deposition temperature of the gaseous silicon source is minimized, and the rate of increase from the cooling temperature to the first deposition temperature is improved. Thus, while ensuring sufficient evaporation of the first solvent from the porous carbon surface, the temperature is further reduced. The evaporation of the solvent inside the porous carbon can raise the temperature to the temperature of the second vapor-phase silicon source deposition in a short time, leaving more of the first solvent inside the porous carbon. This is more conducive to enhancing the adsorption of the vapor-phase silicon source by the subsequent solvent, avoiding silicon deposition on the surface of the porous carbon. At the same time, the PolarClean used in this invention has a high boiling point and a relatively moderate polarity, and has chemical groups that can crosslink with both the silicon deposition layer of the porous silicon-carbon intermediate and the vapor-phase carbon source. It also limits the cooling temperature and the heating rate to the second deposition temperature. This results in better carbon layer coating, further suppressing the expansion of the silicon layer, reducing excessive silicon deposition on the surface of the porous carbon, lowering the resistivity, and extending the cycle life of the battery.

[0050] The present invention also provides a porous silicon-carbon material prepared by the method for preparing the high-capacity, low-expansion porous silicon-carbon material.

[0051] The features and beneficial effects of this invention are as follows:

[0052] This invention provides a high-capacity, low-expansion porous silicon-carbon material and its innovative preparation method. The core of this method lies in the use of a multi-step vapor-phase silicon source deposition process and the creative introduction of two specific organic solvents (a first solvent and a second solvent). This successfully solves the key bottleneck problems that easily occur when vapor-phase depositing silicon on porous carbon with low pore volume and high microporosity, such as internal silicon crystallization, excessive silicon deposition on the outer surface, and the resulting large material expansion, high impedance, and poor cycle life.

[0053] This method first precisely controls two-step vapor-phase silicon source deposition. An organic solvent with a high boiling point and strong physical adsorption or chemical bonding groups for the deposited silicon layer is used as the first solvent to penetrate deep into the porous carbon inner layer to adsorb the silicon source and its deposition intermediates. During the second deposition, the solvent decomposes to form a carbonization layer, effectively isolating the subsequent silicon source from direct contact with the deposited silicon and significantly inhibiting silicon crystallization inside the porous carbon. Subsequently, a second solvent with both high vapor-phase carbon source and high adsorption capacity for deposited silicon is used to promote uniform penetration of the vapor-phase carbon source and coat it into the silicon layer inside the material, forming a buffer layer to inhibit silicon expansion. Finally, on a porous carbon substrate with low pore volume and high microporosity, high silicon loading, uniform amorphous deposition of the inner layer, and stable coating are achieved. The resulting material has high specific capacity, low expansion rate, low impedance, and excellent cycle stability, significantly improving the overall performance of silicon-carbon anodes. Attached Figure Description

[0054] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0055] Figure 1 This is a scanning electron microscope image of Si element in the high-capacity, low-expansion porous silicon-carbon material prepared in Example 1.

[0056] Figure 2 The image shows a scanning electron microscope image of Si in the high-capacity, low-expansion porous silicon-carbon material prepared in Comparative Example 1. Detailed Implementation

[0057] To facilitate understanding of the present invention, a more comprehensive description of the present invention will be given below, and embodiments of the present invention will be provided, but this does not limit the scope of the present invention.

[0058] In order to solve the problems in the prior art of vapor deposition of silicon sources on porous carbon with low pore volume and high porosity, such as crystallization inside the porous carbon pores and excessive deposition of silicon sources on the outer surface, as well as the excessive expansion of silicon-carbon materials caused by this phenomenon, resulting in increased impedance and ultimately reduced battery cycle performance, this invention proposes a multi-step vapor deposition scheme for silicon sources. This invention innovatively proposes a technical solution completely different from direct vapor deposition coating. It adopts a multi-step vapor-phase silicon source deposition process and innovatively utilizes organic solvents with specific cross-linking or adsorption capabilities based on the state and properties of the vapor-phase silicon source during porous carbon deposition. This allows the vapor-phase silicon source and its vapor deposition intermediates to be more adsorbed or bonded to the inner surface of the porous carbon through physical or chemical actions. Combined with the fixation and coating effect of the organic solvent's high-temperature cracking and carbonization, direct contact between the deposited silicon and the secondary introduced vapor-phase silicon source is isolated, avoiding silicon crystallization inside the porous carbon. Furthermore, another organic solvent with the ability to cross-link and adsorb both the deposited silicon and the vapor-phase carbon source in the porous silicon-carbon intermediates is used to further coat the silicon-carbon material after the vapor-phase carbon source is carbonized, suppressing the expansion of the internal silicon layer, thereby reducing impedance and further improving the cycle life of the battery.

[0059] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0060] This invention provides a method for preparing a high-capacity, low-expansion porous silicon-carbon material, comprising the following steps:

[0061] S1: A gaseous silicon source is introduced into the porous carbon heated to the first deposition temperature to carry out a gaseous silicon source deposition reaction, and a partially silicon-deposited porous carbon is obtained. The temperature is lowered to below the boiling point of the first solvent, and the first solvent is mixed evenly with the partially silicon-deposited porous carbon. After heating to the first deposition temperature, a gaseous silicon source is introduced again to carry out a gaseous silicon source deposition reaction, and a porous silicon-carbon intermediate is obtained.

[0062] S2: The second solvent is mixed evenly with the porous silicon-carbon intermediate cooled to below the boiling point of the second solvent. After heating to the second deposition temperature, a mixture of gaseous carbon source and inert gas is introduced to carry out gaseous carbon source deposition reaction, and high-capacity, low-expansion porous silicon-carbon material is obtained.

[0063] The first solvent is an organic solvent that can adsorb the silicon deposition layer in the porous carbon containing the gaseous silicon source and the partially deposited silicon through physical and / or chemical means, and whose boiling point and decomposition temperature are lower than the first deposition temperature.

[0064] The second solvent is an organic solvent that can adsorb gaseous carbon sources and link porous carbon intermediates in a silicon deposition layer through physical and / or chemical means, and whose boiling point and decomposition temperature are lower than the second deposition temperature.

[0065] The first solvent and the second solvent may be the same or different solvents. The first deposition temperature and the second deposition temperature are not specifically limited and are not restricted to the numerical ranges listed in this specification. Those skilled in the art can understand the thermal decomposition characteristics of the gaseous silicon source and the gaseous carbon source based on common knowledge, obtain the thermal decomposition temperature, and optimize and determine the deposition temperature range through conventional experiments to ensure that the gaseous material is effectively decomposed at the deposition temperature and achieves controllable deposition on the porous carbon surface. As an example, the first deposition temperature and the second deposition temperature are each independently a temperature in the range of 350 to 700°C.

[0066] This invention employs a multi-step vapor-phase silicon source deposition strategy and innovatively combines a first solvent and a second solvent to suppress silicon crystallization inside porous carbon pores and excessive deposition on the outer surface of porous carbon. This overcomes the problem that excessive silicon deposition on the outer surface of porous carbon leads to high material resistivity, while the silicon-carbon material expands significantly during full electric cycling, resulting in rapid capacity decay and cycle failure.

[0067] The first solvent exhibits strong physical adsorption and / or chemical cross-linking capabilities with the fumed silicon source and its deposited silicon layer. This capability stems from the strong physical adsorption and cross-linking bonding of the organic solvent with the fumed silicon source and its deposited product. In this case, a two-step fumed silicon source deposition process is performed in S1. In the first step, the fumed silicon source is preferentially deposited within the pores of the porous carbon, while the first solvent is more readily adsorbed within the porous carbon. When the temperature is raised to the first deposition temperature, since the decomposition temperature of the first solvent used in this invention is lower than the deposition temperature of the fumed silicon source, the first solvent can undergo decomposition and carbonization during the heating process, thus avoiding the need for a second introduction of solvent. The fumed silicon source directly contacts the elemental silicon in the semi-deposited silicon-carbon, inhibiting silicon crystallization inside the porous carbon and effectively adsorbing the fumed silicon source into the inner pores. Furthermore, the addition of a second solvent, which simultaneously adsorbs or crosslinks the silicon deposition layer of the porous silicon-carbon intermediate and the fumed carbon source, allows for better penetration into the pores of the porous carbon intermediate while adsorbing the fumed carbon source. Residual solvent on the surface evaporates more readily. This reduces the amount of exposed silicon inside the porous carbon, buffers silicon expansion, lowers impedance, and ultimately improves cycle performance.

[0068] As a further example, the first solvent is selected from organic solvents with a boiling point of 60 to 300°C that can adsorb silicon deposits in porous carbon containing gaseous silicon sources and partial silicon deposits by physical and / or chemical means.

[0069] As a further example, the first solvent is exemplary selected from one of acetonitrile, formamide, glycerol, propylene carbonate, dimethyl sulfoxide, ethylene glycol, dimethylformamide, and nitromethane.

[0070] This invention further optimizes the type of the first solvent, comprehensively considering its boiling point, adsorption capacity for the fumed silicon source, and physical adsorption and chemical bonding capacity for the silicon deposited layer. A higher boiling point of the first solvent shortens the heating time required before the second fumed silicon source is introduced, thereby reducing the volatilization of the first solvent within the porous carbon pores. Furthermore, the type of the first solvent is further optimized based on its adsorption and cross-linking effects on the silicon deposited layer in the porous carbon, ensuring better adsorption and cross-linking of the silicon deposited layer. The combined optimization of these factors enhances the penetration of the first solvent within the porous carbon pores, increases solvent volatilization on the porous carbon surface, and reduces solvent volatilization within the porous carbon pores. This enhances the adsorption of the introduced fumed silicon source within the pores and reduces the deposition of the fumed silicon source on the outer surface of the porous carbon, thereby further reducing the impedance of the silicon-carbon material and improving capacity cycling retention.

[0071] As a further preferred example, the first solvent is selected from organic solvents with a boiling point of 150 to 300°C.

[0072] As a further preferred example, the first solvent is exemplary selected from one or more of glycerol, formamide, dimethyl sulfoxide, and propylene carbonate.

[0073] As a further example, before the first solvent is added in S1, the flow rate of the gaseous silicon source is 6-10 L / min, and after the gaseous silicon source is introduced, the temperature is maintained for 96-160 min.

[0074] After the first solvent is added in S1, the flow rate of the gaseous silicon source is 5-8 L / min, and the temperature is maintained for 45-72 min after the gaseous silicon source is introduced.

[0075] In this invention, the utilization rate of the fumed silicon source can be further controlled by controlling the flow rate of the two fumed silicon sources, thereby controlling the amount of silicon deposited on the porous carbon material. A higher flow rate results in lower utilization of the fumed silicon source, ultimately leading to a decrease in the amount of deposited silicon, resulting in a lower capacity of the silicon-carbon material. Conversely, a lower flow rate, while increasing silicon deposition and thus the capacity of the silicon-carbon material, causes excessively low flow rates to deposit more fumed silicon on the porous carbon surface, leading to expansion and higher resistivity of the silicon-carbon material. Therefore, limiting the flow rate of the fumed silicon source within a certain range can further optimize the amount of silicon deposited on the porous carbon material. Under the action of the first solvent, this optimization of the fumed silicon source flow rate can further reduce the amount of silicon deposited on the outer surface of the silicon-carbon material, lower the impedance, and improve the cycle capacity retention rate. By controlling the time of introducing the gaseous silicon source twice before and after the first solvent is added, and maintaining the temperature, the amount of gaseous silicon source deposited on porous carbon before and after the first solvent is introduced can be regulated. This avoids excessive deposition of gaseous silicon source on the outer surface of porous carbon due to excessive first-time introduction, and also avoids insufficient deposition of gaseous silicon source in the pores of porous carbon due to insufficient first-time introduction. In this case, the first solvent cannot be well adsorbed onto the silicon deposition layer, reducing the amount of carbonization of the first solvent on the silicon deposition layer. As a result, the second gaseous silicon source deposition is more likely to directly contact the deposition layer formed during the first gaseous silicon source deposition, increasing the risk of silicon crystallization, which in turn leads to increased impedance and reduced cycle capacity retention.

[0076] As a further example, the solid-liquid ratio of the first solvent to the partially silicon-deposited porous carbon is (88-93):(7-12).

[0077] The present invention further optimizes the amount of the first solvent to avoid the first solvent being too low, which would result in the first solvent adsorbing too little of the product deposited by the vapor silicon source, thereby affecting the more of the vapor silicon source adsorbed inside the porous carbon.

[0078] As a further example, the cooling temperature in S1 is 1 to 40°C below the boiling point of the first solvent.

[0079] As a further example, the heating rate in S1 to reheat to the first deposition temperature is 40–70 °C / min.

[0080] This invention further limits the cooling temperature. When the cooling temperature is too low, the heating time during the second introduction of the vapor silicon source is too long, resulting in more solvent evaporation in the porous carbon inner layer and more silane deposition on the porous carbon surface, leading to greater expansion. Conversely, when the cooling temperature is too high, some of the first solvent may evaporate during the addition process due to excessive temperature. In this case, the amount of the first solvent entering the porous carbon is too small, leading to the same result as the former. Similarly, a low heating rate during the second deposition of the vapor silicon source also results in more solvent evaporation in the porous carbon inner layer, more vapor silicon source deposition on the surface, greater expansion, and higher resistivity. A high heating rate increases power consumption and affects the lifespan of the equipment.

[0081] As a further example, the second solvent is selected from organic solvents with a boiling point of 60 to 300°C and a silicon deposition layer capable of adsorbing gaseous carbon sources and linking porous carbon intermediates by physical and / or chemical means.

[0082] As a further example, the second solvent is exemplary selected from one or more of toluene, chloroform, PolarClean, cyclohexane, benzene, and aniline.

[0083] The PolarClean is a mixture of methyl 5-(dimethylamino)-2-methyl-5-oxovalerate (1) and N,N,N',N'-2-pentamethylglutaramide (2) in a mass ratio of 20:1.

[0084] As a further example, the second solvent is selected from organic solvents with a boiling point of 100 to 280°C.

[0085] As a further example, the solid-liquid ratio of the second solvent to the porous carbon intermediate is (88-93):(7-12).

[0086] As a further example, the cooling temperature in S2 is 1 to 40°C below the boiling point of the second solvent.

[0087] As a further example, the heating rate in S2 to the second deposition temperature is 40–70 °C / min.

[0088] As a further example, the flow rate of the gaseous carbon source introduced in S2 is 6-10 L / min, and the gaseous carbon source is introduced and kept at a temperature for 96-160 min.

[0089] In this invention, by individually or simultaneously optimizing factors such as the temperature at which the second solvent is cooled to below its boiling point, the rate at which the temperature is raised to the temperature at which the gaseous carbon source is deposited, and the flow rate of the gaseous carbon source, the adsorption capacity of the gaseous carbon source inside the porous carbon can also be affected. This is related to factors such as the volatilization of the second solvent during the heating process and the amount of gaseous carbon source deposited.

[0090] As a further example, the porous carbon has a pore volume of 0.8 ± 0.3 cm³. 3 / g, the microporosity of porous carbon is ≥80%.

[0091] The microporosity refers to the percentage of pores with an average pore size <2 nm in porous carbon, which constitutes the total pore volume.

[0092] This invention can further limit the parameters such as pore volume and microporosity of porous carbon. When the pore volume and microporosity are within a certain range, the appropriate pore volume and microporosity provide sufficient space for the deposition of gaseous silicon source inside the pores of porous carbon. It also avoids the phenomenon that the pore volume is too low and exceeds the limit of silicon deposition. In this case, silicon may be mainly deposited on the surface in the later stage, resulting in a large silicon content on the surface, excessive expansion, high resistivity and other problems. It also avoids the problem that the pore volume of porous carbon is too large. In this case, the microporosity is low, more silicon is deposited on the surface, silicon crystallization is easy to occur, and the resistivity increases.

[0093] As a further preferred example, the specific surface area of ​​the porous carbon is 1500–2500 m². 2 / g.

[0094] As a further preferred example, the porous carbon has a particle size of 2 to 10 μm and an average pore size of 1 to 5 nm.

[0095] As a further example, the gaseous silicon source includes halogen-free silane gaseous silicon sources and halogen-containing silane gaseous silicon sources.

[0096] As a further example, the halogen-free silane-based gaseous silicon source includes one of silane, ethylsilane, and propane.

[0097] As a further example, the halogenated silane gaseous silicon source is selected from one or more of dichlorosilane, trichlorosilane, tetrachlorosilane, and methyltrichlorosilane.

[0098] As a further preferred example, the gaseous silicon source is a silane-based gaseous silicon source.

[0099] As a further preferred example, the gaseous silicon source is silane.

[0100] As a further embodiment, the gaseous carbon source is exemplary selected from one or more of acetylene, ethylene, propylene, methane, ethane, and propane.

[0101] As a further preferred example, the gaseous silicon source is silane, the gaseous carbon source is acetylene, the first solvent is glycerol, the second solvent is PolarClean, the cooling temperature in S1 is 1-20°C below the boiling point of the first solvent, the cooling temperature in S2 is 1-20°C below the boiling point of the second solvent, and the heating rate in S2 to reheat to the first and second deposition temperatures is 55-70°C / min.

[0102] This invention further limits the types of the first and second solvents based on the physicochemical properties of the selected gaseous silicon and carbon sources. Both the first and second solvents are high-boiling-point organic solvents. Because the first solvent, glycerol, has a high penetration effect on the deposited silicon layer of silane and contains numerous chemical groups that bind to the deposited silicon layer, it facilitates the wetting of glycerol within the porous carbon pores and its cross-linking with part of the deposited silicon layer. Simultaneously, by controlling the cooling temperature within a certain range below the boiling point of the first solvent, the difference between the cooling temperature and the deposition temperature of the gaseous silicon source is minimized, and the rate of increase from the cooling temperature to the first deposition temperature is improved. Thus, while ensuring sufficient evaporation of the first solvent from the porous carbon surface, the temperature is further reduced. The evaporation of the solvent inside the porous carbon can raise the temperature to the temperature of the second vapor-phase silicon source deposition in a short time, leaving more of the first solvent inside the porous carbon. This is more conducive to enhancing the adsorption of the vapor-phase silicon source by the subsequent solvent, avoiding silicon deposition on the surface of the porous carbon. At the same time, the PolarClean used in this invention has a high boiling point and a relatively moderate polarity, and has chemical groups that can crosslink with both the silicon deposition layer of the porous silicon-carbon intermediate and the vapor-phase carbon source. It also limits the cooling temperature and the heating rate to the second deposition temperature. This results in better carbon layer coating, further suppressing the expansion of the silicon layer, reducing excessive silicon deposition on the surface of the porous carbon, lowering the resistivity, and extending the cycle life of the battery.

[0103] The present invention also provides a porous silicon-carbon material prepared by the method for preparing the high-capacity, low-expansion porous silicon-carbon material.

[0104] Example 1:

[0105] Step 1: Select a porous carbon material with a specific surface area of ​​1800 m². 2 / g, particle size 2-10µm, average pore size 1-5nm, pore volume 0.8cm³ 3 / g, microporosity 90%;

[0106] Step 2: Place the 1 kg porous carbon particles in a rotary furnace, evacuate three times, heat to 500°C at a heating rate of 13°C / min, then continuously introduce silane at a flow rate of 8 L / min and hold for 120 min, then rapidly cool down to 275°C (only N2 is introduced during cooling), add glycerol with a solid-liquid ratio of 90:10 to the porous carbon and glycerol introduced with silane, and mix thoroughly and evenly with the semi-deposited silicon carbon at a rotation speed of 15 Hz, then rapidly heat to 500°C at a heating rate of 60°C / min, introduce silane at a flow rate of 6 L / min and hold for 60 min;

[0107] Step 3: After obtaining the porous silicon-carbon intermediate, the temperature is lowered to 275℃, and PolarClean (a mixture of methyl 5-(dimethylamino)-2-methyl-5-oxovalerate and N,N,N',N'-2-pentamethylpentadiamide in a mass ratio of 20:1) is added (the solid-liquid ratio of the porous carbon intermediate to PolarClean is 90:10). The mixture is stirred at 15 Hz to ensure thorough and uniform mixing with the porous silicon-carbon intermediate. Then, the temperature is rapidly increased to 500℃ at a heating rate of 60℃ / min and held for 2 hours. A mixture of acetylene and nitrogen gas is introduced at a rate of 6 L / min, with a ratio of 50:50, to obtain CVD-coated porous silicon-carbon.

[0108] Step 4: Combine the negative electrode material with SP and PAA in a ratio of 80:10:10 to form a negative electrode sheet and test its capacity and first efficiency; at the same time, combine it with the NCM positive electrode to form a battery.

[0109] Example 2:

[0110] Unlike Example 1, the porous carbon has a specific surface area of ​​1700 m². 2 / g, pore volume 0.7cm 3 / g, microporosity 92%.

[0111] Example 3:

[0112] Unlike Example 1, the porous carbon has a specific surface area of ​​1900 m². 2 / g, pore volume 0.9cm 3 / g, microporosity 85%.

[0113] Example 4: Steps 2 and 3 differ from Example 1, as follows:

[0114] Step 2: Place the 1 kg porous carbon particles in a rotary kiln, evacuate three times, heat to 500°C at a heating rate of 13°C / min, then continuously introduce silane at a flow rate of 8 L / min and hold for 120 min, then rapidly cool down to 80°C (only N2 is introduced during cooling), add acetonitrile with a solid-liquid ratio of 90:10 to the porous carbon and acetonitrile introduced by the silane, and mix thoroughly and evenly with the semi-deposited silicon carbon at a rotation speed of 15 Hz, then rapidly heat to 500°C at a heating rate of 60°C / min, introduce silane at a flow rate of 6 L / min and hold for 60 min;

[0115] Step 3: After obtaining the porous silicon-carbon intermediate, cool it to about 105℃, add toluene (solid-liquid ratio of porous carbon intermediate to toluene is 90:10) and mix it thoroughly with the porous silicon-carbon intermediate at a speed of 15 Hz. Then heat it rapidly to 500℃ at a heating rate of 60℃ / min and keep it at that temperature for 2 hours. During this period, a mixture of acetylene and nitrogen gas is introduced at a rate of 6 L / min with a ratio of 50:50 to obtain CVD-coated porous silicon-carbon.

[0116] Example 5: Steps 2 and 3 differ from Example 1, as follows:

[0117] Step 2: Place the 1 kg porous carbon particles in a rotary furnace, evacuate three times, heat to 500°C at a heating rate of 13°C / min, then continuously introduce silane at a flow rate of 8 L / min and hold for 2 hours, then rapidly cool down to 80°C (only N2 is introduced during cooling), add the porous carbon with silane introduced and glycerol with a solid-liquid ratio of 92:8, and mix thoroughly with the semi-deposited silicon carbon at a rotation speed of 15 Hz, then rapidly heat to 500°C at a heating rate of 60°C / min, introducing silane at a flow rate of 6 L / min during the heating process and holding for 1 hour;

[0118] Step 3: After obtaining the porous silicon-carbon intermediate, cool it to about 275℃, add PolarClean (made by mixing methyl 5-(dimethylamino)-2-methyl-5-oxovalerate and N,N,N',N'-2-pentamethylpentadiamide in a ratio of 20:1) (the solid-liquid ratio of the porous carbon intermediate to PolarClean is 92:8), and mix it thoroughly with the porous silicon-carbon intermediate at a speed of 15 Hz. Then, heat it rapidly to 500℃ at a heating rate of >50℃ / min and hold it at that temperature for 2 hours. During this period, a mixture of acetylene and nitrogen gas is introduced at a rate of 6 L / min, with a ratio of 50:50, to obtain CVD-coated porous silicon-carbon.

[0119] Example 6: Steps 2 and 3 differ from Example 1, as follows:

[0120] Step 2: Place the 1 kg porous carbon particles in a rotary furnace, evacuate three times, heat to 500°C at a heating rate of 13°C / min, then continuously introduce silane at a flow rate of 10 L / min and hold for 96 min, then rapidly cool down to 80°C (only N2 is introduced during cooling), add the porous carbon with silane introduced and glycerol with a solid-liquid ratio of 90:10, and mix thoroughly with the semi-deposited silicon carbon at a rotation speed of 15 Hz, then rapidly heat to 500°C at a heating rate of 60°C / min, introduce silane at a flow rate of 8 L / min and hold for 45 min;

[0121] Step 3: After obtaining the porous silicon-carbon intermediate, cool it to about 250℃, add PolarClean (made by mixing methyl 5-(dimethylamino)-2-methyl-5-oxovalerate and N,N,N',N'-2-pentamethylpentadiamide in a ratio of 20:1) and mix it thoroughly with the porous silicon-carbon intermediate at a speed of 15 Hz. Then, heat it rapidly to 500℃ at a heating rate of >50℃ / min and hold it at that temperature for 2 hours. Then, introduce a mixed gas of acetylene and nitrogen at a rate of 6 L / min with a ratio of 50:50 to obtain CVD-coated porous silicon-carbon.

[0122] Example 7: Steps 2 and 3 differ from Example 1, as follows:

[0123] Step 2: Place the 1 kg porous carbon particles in a rotary kiln, evacuate three times, heat to 500°C at a heating rate of 13°C / min, then continuously introduce silane at a flow rate of 6 L / min and hold for 160 min, then rapidly cool to 80°C (only N2 is introduced during cooling), add acetonitrile (solid-liquid ratio of 90:10) to the porous carbon with introduced silane, and mix thoroughly with glycerol and semi-deposited silicon carbon at a rotation speed of 15 Hz, then rapidly heat to 500°C at a heating rate of 60°C / min, introduce silane at a flow rate of 5 L / min and hold for 72 min.

[0124] Step 3: After obtaining the porous silicon-carbon intermediate, cool it to about 250℃, add PolarClean (made by mixing methyl 5-(dimethylamino)-2-methyl-5-oxovalerate and N,N,N',N'-2-pentamethylpentadiamide in a ratio of 20:1) and mix it thoroughly with the porous silicon-carbon intermediate at a speed of 15 Hz. Then, heat it rapidly to 500℃ at a heating rate of >50℃ / min and hold it at that temperature for 2 hours. During this time, a mixture of acetylene and nitrogen gas is introduced at a rate of 6 L / min, with a ratio of 50:50, to obtain CVD-coated porous silicon-carbon.

[0125] Example 8: Steps 2 and 3 differ from Example 1, as follows:

[0126] Step 2: Place the 1 kg porous carbon particles in a rotary furnace, evacuate three times, heat to 500°C at a heating rate of 13°C / min, then continuously introduce silane at a flow rate of 8 L / min and hold for 2 hours, then rapidly cool down to 275°C (only N2 is introduced during cooling), add glycerol with a solid-liquid ratio of 90:10 to the porous carbon and glycerol introduced with silane, and mix thoroughly and evenly with the semi-deposited silicon carbon at a rotation speed of 15 Hz, then rapidly heat to 500°C at a heating rate of 50°C / min, introducing silane at a flow rate of 6 L / min during the heating, and hold for 1 hour;

[0127] Step 3: After obtaining the porous silicon-carbon intermediate, cool it to about 275℃, add PolarClean (made by mixing methyl 5-(dimethylamino)-2-methyl-5-oxovalerate and N,N,N',N'-2-pentamethylpentadiamide in a ratio of 20:1) (the solid-liquid ratio of the porous carbon intermediate to PolarClean is 90:10), and mix it thoroughly with the porous silicon-carbon intermediate at a speed of 15 Hz. Then, heat it rapidly to 500℃ at a heating rate of 50℃ / min and hold it at that temperature for 2 hours. During this time, a mixture of acetylene and nitrogen gas is introduced at a rate of 6 L / min, with a ratio of 50:50, to obtain CVD-coated porous silicon-carbon.

[0128] Example 9: Steps 2 and 3 differ from Example 1, as follows:

[0129] Step 2: Place the 1 kg porous carbon particles in a rotary furnace, evacuate three times, heat to 500°C at a heating rate of 13°C / min, then continuously introduce silane at a flow rate of 8 L / min and hold for 2 hours, then rapidly cool down to 250°C (only N2 is introduced during cooling), add glycerol with a solid-liquid ratio of 90:10 to the porous carbon and glycerol introduced with silane, and mix thoroughly and evenly with the semi-deposited silicon carbon at a rotation speed of 15 Hz, then rapidly heat to 500°C at a heating rate of 60°C / min, introducing silane at a flow rate of 6 L / min during the heating, and hold for 1 hour;

[0130] Step 3: After obtaining the porous silicon-carbon intermediate, the temperature is lowered to 250℃, and PolarClean (composed of methyl 5-(dimethylamino)-2-methyl-5-oxovalerate and N,N,N',N'-2-pentamethylpentadiamide in a 20:1 ratio) is added (the solid-liquid ratio of the porous carbon intermediate to PolarClean is 90:10). The mixture is stirred at 15 Hz to ensure thorough and uniform mixing with the porous silicon-carbon intermediate. Then, the temperature is rapidly increased to 500℃ at a heating rate of 60℃ / min and held for 2 hours. During this period, a mixture of acetylene and nitrogen gas is introduced at a rate of 6 L / min in a 50:50 ratio to obtain CVD-coated porous silicon-carbon.

[0131] Example 10: Steps 2 and 3 differ from Example 1, as follows:

[0132] Step 2: Place the 1 kg porous carbon particles in a rotary kiln, evacuate three times, heat to 500°C at a heating rate of 13°C / min, then continuously introduce silane at a flow rate of 7 L / min and hold for 106 min, then rapidly cool to 80°C (only N2 is introduced during cooling), add the porous carbon with silane introduced and glycerol with a solid-liquid ratio of 90:10, and mix thoroughly with the semi-deposited silicon carbon at a rotation speed of 15 Hz, then rapidly heat to 500°C at a heating rate of 60°C / min, introduce silane at a flow rate of 8 L / min and hold for 72 min.

[0133] Step 3: After obtaining the porous silicon-carbon intermediate, cool it to about 250℃, add PolarClean (made by mixing methyl 5-(dimethylamino)-2-methyl-5-oxovalerate and N,N,N',N'-2-pentamethylpentadiamide in a ratio of 20:1) and mix it thoroughly with the porous silicon-carbon intermediate at a speed of 15 Hz. Then, heat it rapidly to 500℃ at a heating rate of >50℃ / min and hold it at that temperature for 2 hours. Then, introduce a mixed gas of acetylene and nitrogen at a rate of 6 L / min with a ratio of 50:50 to obtain CVD-coated porous silicon-carbon.

[0134] Comparative Example 1:

[0135] Step 1: Select a porous carbon material with a specific surface area of ​​1800 m². 2 / g, particle size 2-10µm, average pore size 1-5nm, pore volume 0.8cm³ 3 / g, microporosity 90%;

[0136] Step 2: Place the 1 kg porous carbon particles in a rotary kiln, evacuate the vacuum three times, heat to 500°C at a heating rate of 13°C / min, then continuously introduce silane at a flow rate of 8 L / min and keep at the temperature for 2 hours, then introduce silane at a flow rate of 6 L / min and keep at the temperature for 1 hour.

[0137] Step 3: A mixture of acetylene and nitrogen gas is introduced at a rate of 6 L / min, with a ratio of 50:50, to obtain CVD-coated porous silicon-carbon.

[0138] Step 4: Combine the negative electrode material with SP and PAA in a ratio of 80:10:10 to form a negative electrode sheet and test its capacity and first efficiency; at the same time, combine it with the NCM positive electrode to form a battery.

[0139] Comparative Example 2:

[0140] The difference between step 1 and Example 1 is as follows:

[0141] Step 1: Select a porous carbon material with a specific surface area of ​​800 m². 2 / g, particle size 2-10µm, average pore size 1-5nm, pore volume 0.4cm³ 3 / g, microporosity 95%.

[0142] Comparative Example 3:

[0143] Step 1: Select a porous carbon material with a specific surface area of ​​1800 m². 2 / g, particle size 2-10µm, average pore size 1-5nm, pore volume 0.8cm³ 3 / g, microporosity 90%;

[0144] Step 2: Place the 1 kg porous carbon particles in a rotary kiln, evacuate three times, heat to 500°C at a heating rate of 13°C / min, then continuously introduce silane at a flow rate of 8 L / min and keep warm for 2 hours, then rapidly cool down to 62°C (only N2 is introduced during cooling), add water with a solid-liquid ratio of 90:10 to the porous carbon and water introduced with silane, and mix thoroughly and evenly with glycerol and semi-deposited silicon carbon at a rotation speed of 15 Hz, then rapidly heat to 500°C at a heating rate of 60°C / min, introduce silane at a flow rate of 6 L / min and keep warm for 1 hour.

[0145] Step 3: After obtaining the porous silicon-carbon intermediate, cool it to 35℃, add water and mix it thoroughly with the porous silicon-carbon intermediate at 15 Hz. Then, rapidly heat it to 500℃ at a heating rate of 60℃ / min and hold it at that temperature for 2 hours. A mixture of acetylene and nitrogen gas (50:50 ratio) is introduced at a rate of 6 L / min to obtain CVD-coated porous silicon-carbon.

[0146] Step 4: Combine the negative electrode material with SP and PAA in a ratio of 80:10:10 to form a negative electrode sheet and test its capacity and first efficiency; at the same time, combine it with the NCM positive electrode to form a battery.

[0147] The following electrochemical performance tests were performed on Examples 1-9 and Comparative Examples 1-2:

[0148] At 25℃, the battery capacity and resistivity were recorded by performing charge-discharge cycles at 0.33C / 0.33C. The electrode expansion rate at different stages of the cycle and the capacity retention rate at different cycle numbers were also recorded.

[0149] Table 1 shows the electrochemical performance test results of Examples 1-9 and Comparative Examples 1-2.

[0150] Table 1

[0151]

[0152] As can be seen from the comparison between Examples 1-10 and Comparative Examples 1-3, Examples 1-10 are significantly better than Comparative Examples 1-2 in terms of electrode impedance and capacitance retention.

[0153] Comparative Example 1 involves low-temperature treatment of porous carbon material without the use of the first and second solvents. In this case, due to the lack of adsorption of the gaseous silicon source and its deposition products inside the porous carbon by the first solvent and the adsorption of the gaseous carbon source by the second solvent, most of the gaseous silicon source on the porous carbon is deposited on the surface of the porous carbon. Due to the lack of buffering and confinement of the porous carbon pores, the expansion rate of the electrode is greatly increased, reaching as high as 100%. At this time, the capacity retention rate is extremely low at 500 cycles, only 65%. In Comparative Example 2, because the microporosity and pore volume of the porous carbon are not within the specified range and the specific surface area is small, the first and second solvents may not be able to fill the pores of the porous carbon well, resulting in insufficient wetting inside the porous carbon. Consequently, there is a lack of adsorption of the gaseous silicon source and gaseous carbon source by the solvents. At this time, more silicon is deposited on the outside of the porous carbon, resulting in a lower capacity retention rate of the silicon-carbon material.

[0154] Comparing Example 1 and Comparative Example 3, when the first and second solvents used are not within the scope of this invention, and the first solvent lacks chemical groups that can connect with the silicon deposition layer in the porous carbon partially deposited by physical and / or chemical means, and the second solvent lacks chemical groups that can simultaneously connect with the porous silicon-carbon intermediate and the gaseous carbon source by physical and / or chemical means, the lack of good adsorption or cross-linking effect on the gaseous silicon source and gaseous carbon source prevents the adsorption of the gaseous carbon source or gaseous silicon source inside the porous carbon, inhibiting silicon crystallization and extending battery cycle life, as described in this invention. However, Example 1... Figures 1-2As can be seen, silicon deposition is more uniform in Example 1, resulting in higher capacity, lower expansion rate, and better cycling performance.

[0155] Comparing Examples 1 and 2-3, it can be seen that when the pore volume and microporosity of the porous carbon are further optimized, the suitable pore volume and microporosity provide sufficient space for the first and second solvents to wet the interior of the porous carbon. This allows for better adsorption of the vapor-phase silicon source and its deposition intermediates by the first solvent within the porous carbon, as well as adsorption of the vapor-phase carbon source by the second solvent. Furthermore, the suitable pore volume and microporosity also provide adequate space for the deposition of the vapor-phase silicon source on the porous carbon. This ensures sufficient space for the vapor-phase silicon source to deposit within the porous carbon, preventing excessive silicon deposition on the surface and avoiding excessively large pores that could lead to silicon crystallization and increased battery impedance. Based on this, Example 1 exhibits better cycle capacity retention and lower electrode expansion rate.

[0156] A comparison of Examples 1 and 4-5 shows that Example 4 used acetonitrile, which has a relatively low boiling point, as the first solvent. However, due to the significant difference between the deposition temperature of the fumed silicon source and the boiling point of acetonitrile, and because acetonitrile has a weaker wetting ability and fewer chemical cross-linking groups compared to glycerol, the heating time during the second introduction of the fumed silicon source was longer. This resulted in a decrease in the content of the first solvent in the inner layer due to the longer heating time, leading to a reduced adsorption of the fumed silicon source by the first solvent, more silicon deposition on the porous carbon surface, and higher resistivity. Example 5 used a lower solvent ratio. In this case, the lack of good wetting ability affected the adsorption of more fumed silicon source into the porous carbon, and also affected the decomposition and deposition of the fumed carbon source within the pores.

[0157] A comparison of Examples 1 and 6-7, 10 shows that during the first and second vapor-phase silicon source deposition, a higher silane introduction rate results in a lower silicon content. While this achieves lower battery impedance and expansion rate, it also leads to lower capacity of the silicon-carbon material and lower initial battery efficiency. Conversely, a lower silane introduction rate results in higher capacity due to more silicon deposition, but excessive silicon deposition leads to higher surface silicon content, increasing impedance and expansion rate. Therefore, further optimizing the silane introduction rates can better balance battery capacity, impedance, and cycle capacity retention. Furthermore, comparing Examples 1 and 10, controlling the time of vapor-phase silicon source introduction and heat preservation before and after the first solvent introduction can regulate the amount of vapor-phase silicon deposited on porous carbon before and after the first solvent introduction. This avoids the problem of insufficient vapor-phase silicon source deposition in the porous carbon pores due to insufficient first-time vapor-phase silicon source introduction, which prevents the first solvent from being properly adsorbed onto the silicon deposition layer.

[0158] A comparison of Examples 1 and 8-9 shows that by optimizing the heating rate during the second addition of the fumed silicon source within a certain range, or by limiting the cooling temperature within a certain range, the cycle stability of the battery can be further improved. This avoids excessive evaporation of the solvent in the porous carbon inner layer at a lower heating rate, weakens the adsorption effect of the first solvent on the surface silicon, and may lead to increased crystallization inside the porous carbon, resulting in increased resistivity. It also avoids excessively low cooling temperatures, which would increase the time to heat up from low temperature to high temperature, leading to increased evaporation of the inner layer solvent and the same problem as excessively low heating rates.

[0159] In summary, this invention provides a high-capacity, low-expansion porous silicon-carbon material and its innovative preparation method. The core of this invention lies in the use of a multi-step vapor-phase silicon source deposition process and the creative introduction of two specific organic solvents (a first solvent and a second solvent). This successfully solves the key bottleneck problems that easily occur during vapor-phase deposition of silicon on porous carbon with low pore volume and high microporosity, such as internal silicon crystallization, excessive silicon deposition on the outer surface, and the resulting large material expansion, high impedance, and poor cycle life. As a result, a high-capacity, low-expansion porous silicon-carbon material is obtained.

[0160] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing a high-capacity, low-expansion porous silicon-carbon material, characterized in that, Includes the following steps: S1: A gaseous silicon source is introduced into the porous carbon heated to the first deposition temperature to carry out a gaseous silicon source deposition reaction, and a partially silicon-deposited porous carbon is obtained. The temperature is lowered to below the boiling point of the first solvent, and the first solvent is mixed evenly with the partially silicon-deposited porous carbon. After heating to the first deposition temperature, a gaseous silicon source is introduced again to carry out a gaseous silicon source deposition reaction, and a porous silicon-carbon intermediate is obtained. S2: The second solvent is mixed evenly with the porous silicon-carbon intermediate cooled to below the boiling point of the second solvent. After heating to the second deposition temperature, a mixture of gaseous carbon source and inert gas is introduced to carry out gaseous carbon source deposition reaction, and high-capacity, low-expansion porous silicon-carbon material is obtained. The first solvent is an organic solvent that can adsorb the silicon deposition layer in the porous carbon containing the gaseous silicon source and the partially deposited silicon through physical and / or chemical means, and whose boiling point and decomposition temperature are lower than the first deposition temperature. The second solvent is an organic solvent that can adsorb gaseous carbon sources and link porous carbon intermediates in a silicon deposition layer through physical and / or chemical means, and whose boiling point and decomposition temperature are lower than the second deposition temperature.

2. The method for preparing high-capacity, low-expansion porous silicon-carbon material according to claim 1, characterized in that, The first solvent is selected from organic solvents with a boiling point of 60 to 300°C that can adsorb the silicon deposited layer in porous carbon and part of the silicon deposited by physical and / or chemical means. Preferably, the first solvent is selected from one of acetonitrile, formamide, glycerol, propylene carbonate, dimethyl sulfoxide, ethylene glycol, dimethylformamide, and nitromethane; More preferably, the first solvent is selected from one or more of glycerol, formamide, dimethyl sulfoxide, and propylene carbonate.

3. The method for preparing high-capacity, low-expansion porous silicon-carbon material according to claim 1, characterized in that, Before the first solvent is added in S1, the flow rate of the gaseous silicon source is 6-10 L / min, and after the gaseous silicon source is introduced, the temperature is maintained for 96-160 min. After the first solvent is added in S1, the flow rate of the gaseous silicon source is 5-8 L / min, and the temperature is maintained for 45-72 min after the gaseous silicon source is introduced.

4. The method for preparing high-capacity, low-expansion porous silicon-carbon material according to claim 1, characterized in that, The solid-liquid ratio of the first solvent to the partially silicon-deposited porous carbon is (88-93):(7-12); The solid-liquid ratio of the second solvent to the porous carbon intermediate is (88-93):(7-12).

5. The method for preparing high-capacity, low-expansion porous silicon-carbon material according to claim 1, characterized in that, The cooling temperature in S1 is 1–40°C below the boiling point of the first solvent. Preferably, the heating rate in S1 for reheating to the first deposition temperature is 40–70 °C / min.

6. The method for preparing high-capacity, low-expansion porous silicon-carbon material according to claim 1, characterized in that, The second solvent is selected from organic solvents with a boiling point of 60 to 300°C and a silicon deposition layer capable of adsorbing gaseous carbon sources and linking porous carbon intermediates by physical and / or chemical means; Preferably, the second solvent is selected from one or more of toluene, chloroform, PolarClean, cyclohexane, benzene, and aniline.

7. The method for preparing high-capacity, low-expansion porous silicon-carbon material according to claim 1, characterized in that, The cooling temperature in S2 is 1–40°C below the boiling point of the second solvent. Preferably, the heating rate in S2 to the second deposition temperature is 40–70 °C / min; Preferably, the flow rate of the gaseous carbon source introduced in S2 is 6-10 L / min, and the temperature is maintained for 96-160 min after the gaseous carbon source is introduced.

8. The method for preparing high-capacity, low-expansion porous silicon-carbon material according to claim 1, characterized in that, The porous carbon has a pore volume of 0.8 ± 0.3 cm³. 3 / g, the microporosity of porous carbon is ≥80%; Preferably, the specific surface area of ​​the porous carbon is 1500–2500 m². 2 / g; Preferably, the porous carbon has a particle size of 2–10 μm and an average pore size of 1–5 nm.

9. The method for preparing high-capacity, low-expansion porous silicon-carbon material according to claim 1, characterized in that, The gaseous silicon source is silane, the gaseous carbon source is acetylene, the first solvent is glycerol, the second solvent is PolarClean, the cooling temperature in S1 is 1-20°C below the boiling point of the first solvent; the cooling temperature in S2 is 1-20°C below the boiling point of the second solvent; the heating rate in S2 to reheat to the first deposition temperature and the second deposition temperature is 55-70°C / min.

10. A porous silicon-carbon material prepared by the method for preparing the high-capacity, low-expansion porous silicon-carbon material according to any one of claims 1 to 9.